TAGLINE "ADA AQUA" EFFECTIVENESS USING EPIC MODEL IN KELURAHAN RANGKAPAN JAYA BARU PANCORAN MAS DEPOK - Ade Purwanto; Khoirul Umam (Jurnal Manajemen Pemasaran, 2019)
One measure of the success of advertising is its ability to create perspective space in the minds of audiences and consumers. Advertising as a message delivery tool does not only function to provide information, is persuasive and reminds audiences, but must also have an impact on consumers in the form of purchasing actions and attitudes towards products as expected by producers. This study aims to analyze the impact of AQUA product advertisements with the tagline “Ada AQUA” to consumers by using the EPIC model (Emphaty, Persuation, Impact, Communication). The research method used is quantitative descriptive. The results showed that AQUA ads with the tagline "Ada AQUA" were in the effective category as evidenced by the results of Emphaty dimensions of 4.15, which meant consumers liked and were interested in AQUA ads, Persuation dimensions of 3.89 showed AQUA ads were able to strengthen their image and character in the minds of consumers, the Impact dimension of 3.93 shows consumers more easily recognize AQUA ads with that tagline and Communcations dimensions of 4.06 indicate consumers are able to remember AQUA ads well. Broadly speaking, the conclusions obtained are AQUA ads with the tagline “Ada AQUA” effective in delivering the message to the target audience (consumers)